Analysis of software methods for metal computed tomography artifact reduction: experimental research - A. V. Petraikin; Yu. A. Vasilev; Z. R. Artyukova; A. K. Smorchkova; D. S. Semenov; А. А. Baulin; A. A. Alikhanov; R. A. Erizhokov; O. V. Omelyanskaya (Исследования и практика в медицине, 2024)
X‑ray density of biological tissues is an important diagnostic parameter. Metal structures in the CT scanning area distort it, creating artifacts. Thus, hip joint endoprostheses (HJE) often complicate visualization of nearby soft tissue structures of the pelvic organs, which can interfere with the qualitative and quantitative analysis of changes when assessing the prevalence of the oncological process in this area. It is possible to correct these distortions using software methods, bringing the Hounsfield units (HU) values closer to the true ones.Purpose of the study. To conduct a visual (qualitative) and quantitative assessment of metal artifacts in CT images using software methods for their reduction.Materials and methods. A phantom was used for quantitative assessment: a plexiglass cylinder with a HJE in the center and test tubes with potassium hydrophosphate solution around it. The study was performed on a CT scanner with (FBP, iDose, iMR) reconstruction algorithms and O‑MAR technology for artifact suppression. The mean values and standard deviation of HU, the degree of susceptibility to artifacts were measured. Image quality was visually assessed using a five‑point Likert scale.Results. The use of the O‑MAR algorithm does not distort HU in the absence of an HJE and smoothens the HU distribution in its presence. Deviation from the specified values at the level of the HJE neck decreased from 32–36 HU without O‑MAR to ‑1.5 – ‑4.7 HU with O‑MAR. The minimum noise was observed for iMR with O‑MAR at the level of the neck (31.6 HU) and stem (6.2 HU) of the HJE, the maximum – for FBP without O‑MAR (77.0 and 33.2 HU, respectively). The quality assessment was best for iMR with O‑MAR (3 points), the worst for FBP without O‑MAR (1.4 points). It was also shown that O‑MAR forms additional artifacts near the HJE.Conclusion. Metal artifact reduction algorithms do not distort the X‑ray density without an artifact source. In the presence of metal structures, the algorithms reduce HU deviations and improve visualization, but they can form additional artifacts in the form of areas of increased and decreased density, so it is necessary to combine them with reconstruction without artifact reduction. To reduce the noise level, as well as to increase the contrast sensitivity, the use of model iterative reconstruction technology is optimal.